Investigations of surface morphology and chemical composition of Ag/ZnS/glassceramic thin-film structure - Kurbatov, D.; Opanasyuk, A.; Denisenko, V.; Kramchenkov, A.; Zaharets, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The surface morphology and chemical composition of Ag/ZnS/glassceramic thin-film system obtained by close-spaced vacuum sublimation technique under different grow conditions were investigated. Examination of surface profile and morphology was performed by scanning electron and optical microscopy. Chemical composition was studied by Rutherford back scattering method. Results of morphology studies enabled to determine dependence of the growth mechanism, roughness Ra, grain size D of ZnS layers on the growth conditions. The researches of chemical composition allowed to determine the concentration of compound elements and impurities, deviation from stoichiometry and thickness distribution of chemical elements.